Neuroprotective Effects of Oxymatrine on PI3K/Akt/mTOR Pathway After Hypoxic-Ischemic Brain Damage in Neonatal Rats - Wei, Wei; Lu, Min; Lan, Xiao-bing; Liu, Ning; Su, Wei-ke; Dushkin, Alexandr V.; Yu, Jian-qiang (Frontiers in Pharmacology, 2021)
Oxymatrine (OMT), a quinolizidine alkaloid extracted from traditional Chinese herb Sophora flavescens Ait, has drawn attention because of its beneficial bioactivities against hypoxic–ischemic brain damage (HIBD). However, the underlying molecular mechanism remains unclear. In this study, we determined the in vivo and in vitro effects of OMT on seven-day old Sprague-Dawley rats with HIBD and in a rat model of primary hippocampal neuron oxygen glucose deprivation reoxygenation (OGD/R). This study was aimed to evaluate whether OMT exerted neuroprotective effects mediated by the (phosphatidylinositol 3-kinase/protein kinase B/ mammalian target of rapamycin) PI3K/Akt/mTOR pathway after HIBD. Experimental results showed that the alkaloid significantly improved the early neurofunctional development, brain water content, abnormal pathological changes, and necrosis of neurons after HIBD. Moreover, OMT enhanced the cell viability and stabilized the mitochondrial permeability transition pore in the primary hippocampal neurons after OGD/R. OMT significantly decreased the autophagosome generation, elevated the expression of PI3K, Akt, and mTOR, and simultaneously reversed the mRNA expression of microtubule-associated protein 1-light chain 3 (LC3), Beclin-1, and sequestosomel (P62) induced by hypoxia and ischemia. However, these protective effects against HIBD could be suppressed when rapamycin, a specific inhibitor of mTOR, was included. Hence, the OMT exerted neuroprotective effects against HIBD by attenuating excessive autophagy by mediating the PI3K/Akt/mTOR pathway.